Circonscrire le spectre de la vérité : l’écriture du deuil traumatique dans Le jour où je n’étais pas là d’Hélène Cixous - Frédérique Collette (Itinéraires, 2023)
In Le jour où je n’étais pas là, Hélène Cixous looks back, forty years after the event, at the death of her first child, Georges: her son with Down’s syndrome whom she had abandoned to her own mother, Ève. Not only was the author-narrator absent at the time of her child’s death, but so was Ève, making the circumstances of this death a well-kept secret, to which it is impossible to testify with certainty. The author-narrator therefore undertakes to untangle the events preceding this sudden death in a text which—like the son, whose specter only returns to better flee—sets in motion a collapse of the trauma testimony. Indeed, dream and reality, lie and truthfulness, haunting and stream of consciousness overlap in a porous prose that will not quite shed light on the cause of the death. This article therefore intends to show how, in this work, traumatic mourning generates an affabulatory writing which confuses the reader and illustrates the failure of testimony, from which truth constantly escapes. After having defined the notion of traumatic loss, as well as the links uniting the experiences of mourning and trauma, the article’s author will analyze this affabulatory aesthetic through which Cixous implements her traumatic mourning, striving less to piece together the facts surrounding her baby’s death than to imagine, or even deny, what might have happened.